The Effectiveness of Self Instructional Module on Knowledge Regarding Maternal and Neonatal Outcome of Induction of Labour among Staff Nurses in Selected Hospital, Bangalore, India - Shrestha, Rina (Journal of Advanced Academic Research, 2018)
Background of the study Induction of labour is the stimulation of uterine contraction priority to the onset of spontaneous labour. It is an obstetrics intervention that should be used when elective birth will be beneficial to mother and baby. It means initiation of uterine contractions by any method (medical, surgical or combined) for the purpose of vaginal delivery. Objectives • To assess the existing knowledge of staff nurses regarding maternal and neonatal outcome of induction of labour. • To evaluate the effectiveness of self instructional module regarding maternal & neonatal outcome of induction of labour among staff nurses. • To associate pre-test knowledge of staff nurses regarding maternal and neonatal outcome of induction of labour with their selected demographic variables. Methods A Pre experimental design (one group pre and post test design) was conducted at ESI Hospital, Bangalore, 60 samples, non-probability convenient sampling technique, structured questionnaire were developed and validated by experts; the reliability that is test retest method was used, administered self instructional module and conducted post test. The Collected data were analyzed by using descriptive and inferential statistics. Major findings of the study Majority of staff nurses attained were 31-35 years age (37%) had GNM education (83%). About 39% of subjects had above 6 years experiences. SIM is effective in improving staff nurses knowledge regarding maternal and neonatal outcome of induction of labour. (P< 0.05). A significant association was found between knowledge of staff nurses with demographic variables such as age, religion, marital status, educational qualification, total years experiences, monthly income, and previous sources of information. Interpretation and conclusion The findings revealed that the improvement Mean score of all level of knowledge of staff nurses between pre test and post test was 13.75% with ‘t’ test value was 12.88, which was highly significant at p< 0.05. Hence, it is inferred that there is significant increase in the knowledge level of the staff nurses regarding maternal and neonatal outcome of induction of labour after used of Self Instructional Module.